Analysis Determinants Of Anxiety In Pregnancy - Ramadhana Alya Nuur Afifah; Darmayanti Wulandatika; Siti Fatimah (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Background: pregnancy is a natural process that is accompanied by physical and psychological changes. These changes can trigger mental disorders such as anxiety, especially if they are not properly managed. These conditions can have an impact on the health of the mother and fetus. Objective: This study aims to identify the prevalence of anxiety in pregnant women in the city of Banjarmasin and analyze the relationship between age, parity, education, income, and employment with anxiety during pregnancy. Methods: this study uses a quantitative approach with cross-sectional design. A total of 33 participants were selected using purposive sampling technique. The data was collected using the Perinatal Anxiety Screening Scale (PASS) instrument to measure anxiety events during pregnancy. Data analysis was conducted by Spearman Rank test to determine the relationship between the variables studied. Results: this study showed that as many as 66.7% of pregnant women experienced anxiety during pregnancy. In addition, there is a significant relationship between age, parity, education level, income, and employment status with the level of anxiety experienced. Conclusion: the results of this study suggest that performing anxiety screening during pregnancy is important to detect psychological disorders.